Wanted! Free trade agreements in the service of environmental and climate protection - Julia Gruebler; Roman Stöllinger; Gabriele Tondl (The Vienna Institute for International Economic Studies (wiiw), 2021)
The effects of international trade on the planet's climate and environment are manifold and complex. This makes assessment of the impact of free trade agreements (FTAs) a delicate matter. This study provides an overview of the development of sustainability chapters in FTAs and discusses their potential and limitations. It highlights particular industry-specific environmental issues related to EU trade, especially with developing countries, and presents complementary policy options. In this vein, it zooms in on the EU-Mercosur FTA, for which a political agreement was reached in June 2019. It contrasts the estimated cost of increased CO2 emissions attributable to intensified trade relations, as one element of the 'pains from trade', with the estimated 'gains from trade' arising from lower prices for consumers. The analysis suggests that the benefits outweigh the costs; yet, the result is sensitive to assumed prices for pollutants. Furthermore, the effectiveness of the incorporated sustainability chapter is limited by its enforceability. The latter provokes a discussion on the modernisation of the framework of the World Trade Organization, which currently does not allow environmental challenges to be tackled effectively.
Keywords: F13; F14; F18; F64; O13; Q56; 330; free trade agreements; trade policy; environment; sustainability; WTO; Mercosur